Kecerdasan Buatan (AI) dalam Akuntansi : Mengoptimalkan Proses Keuangan dan Pengambilan Keputusan - Lu'ai, Yusril Zam Zami (Maliki Interdisciplinary Journal, 2025)
Artificial Intelligence (AI) is a field of computer science that focuses on developing systems and machines capable of performing tasks that typically require human intelligence. In its development, AI is also used to optimize accounting processes. The method used in this research is literature review. The literature review was conducted by collecting and analyzing various relevant references regarding the influence of AI development in accounting processes. The results obtained indicate that the utilization of AI in accounting systems has resulted in significant changes, which have an impact on increasing efficiency, accuracy, transparency, productivity, and the quality of financial reports. In addition, AI also plays an important role in fraud detection and predictive analysis in the accounting proces.